The efficacy of Dexamethasone in the prevention of postoperative nausea and vomiting after laparoscopic cholecystectomy - Adra, Lama; Ibrahim, Tyseer; ALaji, Bahaa (Latakia University Journal -Medical Sciences Series, 2018)
This study was carried out in the department of anesthesia at Tishreen university hospital , Lattakia , Syria , during the year 2016-2017 . A total of 120 patients , aged between 30 and 50 years old , posted for elective laparoscopic cholecystectomy under general anesthesia belonging to the American society of Anesthesiologist (ASA) physical status ǀ-ǀǀ were included in the study . Patients were divided into three groups : patients in the first group received 2 ml normal saline ( group A ) . Patients in the second group D1 received 8 mg Dexamethasone preoperatively . Patients in the third group D2 received 8 mg immediately after removing the gallbladder from her place. The gall of the study was to show the efficacy of Dexamethasone in the prevention of postoperative nausea and vomiting . the result was better in the second group and the conclusion is that Dexamethasone is effective in prevention of PONV and it is better when we use dexamethasone preoperatively . فعالية الديكساميتازون في الوقاية من الغثيان والإقياء في فترة ما بعد جراحة استئصال المرارة بالتنظير أجريت هذه الدراسة في قسم التخدير والإنعاش في مشفى تشرين الجامعي في اللاذقية خلال العامين 2016-2017 . تضمنت هذه الدراسة 120 مريض أجري لهم استئصال مرارة بالتنظير تحت التخدير العام وينتمون إلى تصنيف الجمعية الأمريكية للتخدير ASA ǀ-ǀǀ . قسم المرضى إلى ثلاثة مجموعات : المجموعة الأولى أعطيوا 2 مل سيروم مالح سوي التوتر (المجموعة A ) ، المرضى في المجموعة الثانية D1 أعطيوا 8 ملغ ديكساميتازون كتحضير دوائي . المرضى في المجموعة الثالثة D2 أعطيوا 8 ملغ ديكساميتازون بعد تسليخ المرارة من كامل مسكنها . هدف البحث هو لإظهار فعالية الديكساميتازون في الوقاية من الغثيان و الإقياء بعد العمل الجراحي . كانت النتائج أفضل في المجموعة الثانية ، والخلاصة هي أن الديكساميتازون فعال في الوقاية من الغثيان و الإقياء بعد العمل الجراحي و من الأفضل إعطاءه كتحضير دوائي .